COMPUTATIONAL STUDY OF THE INTERACTION IN LIGAND-RECEPTOR CYP450-ESTEROL 14 - DEMETHYLASE MYCOBACTERIUM TUBERCULOSIS - Solís C., Christian (2004)
The cytochrome P450 14alpha-sterol demethylase is an enzyme of the Mycobacterium tuberculosis (MT) that by redundancy of its gene that codifies it in the genome of MT should have preponderant rolls for the survival of the pathogen. Using the published models of the structure 3D of this enzyme, we evaluated by «docking» computational method interaction of this protein to ligands of azole type, those that were modeled by geometric optimization and present values of LogP up to 4,9, which indicates their extreme lipophilicity, being observed with clotrimazole the best values for its docking with the protein.